Konsep Ittiḥād dalam Fabel Mantiq at-Ṭair: Pemikiran Tasawuf Falsafi Farīduddīn ‘Aṭār (1145-1221 M) - Muhammad Ihza Fazrian; A.Anjasyah; Sulistiyo (UIN Sunan Kalijaga Yogyakarta, 2023)
This article focuses on Farīduddīn ‘Aṭār 's philosophy of Sufism, namely the concept of ittihad. His thoughts on ittihad can be explored through his work in the form of a fable entitled Mantiq at-Ṭair (The Deliberation of Birds). The fable tells the story of birds that gather and deliberate to find their King named Simurgh. Everything contained in the work is a reflection of ‘Aṭār 's own Sufistic experience in seeking God which is retold through fables. In general, the concept of ittihad was initiated by Abu Yazid al-Bustami, ‘Aṭār developed the concept through his work. Regarding the process of ittihad, in his work ‘Aṭār tells the story of the seven valleys that birds must pass through in search of Simurgh; ṭalab (search), ‘isyq (love), ma'rifat (knowledge), istighnā (the absurdity of things around), tawhīd (unity), hīraṭ (confusion), and fana. The valleys are described as challenges that must be overcome by a Sufi who wants to find his God. The journey ends with the transience of the birds (Sufis) towards other than the Simurgh (God) to cause devotion to Him. This research uses descriptive-analytic method with data obtained from relevant literature sources to build structured and systematic findings. The findings in this article show that the concept of ittihad developed by ‘Aṭār emphasizes the aspects of ‘isyq and fana to find God.